The construction of a novel luminescent lanthanide framework for the selective sensing of Cu2+ and 4-nitrophenol in water. Issue 5 (21st January 2021) - Lin, Zeng-Gang; Song, Fu-Qiang; Wang, Hui; Song, Xue-Qin; Yu, Xin-Xin; Liu, Wei-sheng
Abstract : Two water stable Ln-MOFs that take the (4, 4, 4)-connected nets with unprecedented topology symbol of {4 2 ·6·8 3 }2 {4 2 ·6 2 ·8 2 }{4 2 ·8 4 } were developed for sensing Cu 2+  and 4-NP in aqueous media with high selectivity and sensitivity. Abstract : It is challenging to develop highly stable lanthanide luminescent sensors for detecting heavy metal ions and nitroaromatics in view of the human health and environmental security. To this end, two water stable Ln-MOFs with the chemical constitution of {[Ln(HL)]·3DMF·3H2 O} n (Ln = Eu, LZG-Eu and Ln = Tb, LZG-Tb ) have been developed solvothermally using a multidentate ligand (H4 L ) with the central phenyl backbone bisubstituted by 2, 6-pyridine-dicarboxylic acid at the para -position, H4 L = 1, 4-bis(2′, 2′′, 6′, 6′′-tetracarboxy-1, 4′:4, 4′′-pyridyl)benzene. Single crystal analysis demonstrates that two novel Ln-MOFs feature 4, 4, 4-connected nets with an unprecedented topology symbol of {4 2 ·6·8 3 }2 {4 2 ·6 2 ·8 2 }{4 2 ·8 4 } and contain two kinds of one-dimensional channels. Powder X-ray diffraction as well as the luminescence determination results indicate that they retain their crystallinity and structural integrity in harsh acidic and basic conditions with pH in the range of 4–11. Moreover, they are highly luminescent, which makes them excellent chemical sensors for detecting Cu 2+ and 4-NP (4-nitrophenol) with high selectivity and sensitivity in aqueous media such as deionized water, tap water, and river water based on distinct quenching effects. To the best of our knowledge, their detection limits are lower than those documented so far. In addition, the quenching efficiency of 4-NP was retained in the presence of interfering ions even after the compounds were used for five cycles, which makes them attractive, reliable, visual, and recyclable luminescent Ln-MOF sensor materials for 4-NP. The recognition mechanism for Cu 2+ could be attributed to the dissociation of the main framework induced by Cu 2+ and the subsequent formation of a Cu 2+ coordination species and that for 4-NP is considered to be multi-quenching mechanisms dominated by competition absorption.